Improved synthesis of 6-bromo-7-[11C]methylpurine for clinical use - Toshimitsu Okamura; Tatsuya Kikuchi; Masanao Ogawa; Ming-Rong Zhang (EJNMMI Radiopharmacy and Chemistry, 2024)
Abstract Background Multidrug resistance-associated protein 1 (MRP1), an energy-dependent efflux pump, is expressed widely in various tissues and contributes to many physiological and pathophysiological processes. 6-Bromo-7-[11C]methylpurine ([11C]7m6BP) is expected to be useful for the assessment of MRP1 activity in the human brain and lungs. However, the radiochemical yield (RCY) in the synthesis of [11C]7m6BP was low, limiting its clinical application, because the methylation of the precursor with [11C]CH3I provided primarily the undesired isomer, 6-bromo-9-[11C]methylpurine ([11C]9m6BP). To increase the RCY of [11C]7m6BP, we investigated conditions for improving the [11C]7m6BP/[11C]9m6BP selectivity of the methylation reaction. Results [11C]7m6BP was manually synthesized via the methylation of 6-bromopurine with [11C]CH3I in various solvents and at different temperatures in the presence of potassium carbonate for 5 min. Several less polar solvents, including tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), and ethyl acetate (AcOEt) improved the [11C]7m6BP/[11C]9m6BP selectivity from 1:1 to 2:1, compared with the conventionally used solvents for the alkylation of 6-halopurines, acetone, acetonitrile, and N,N-dimethylformamide. However, a higher temperature (140 °C or 180 °C) was needed to progress the 11C-methylation in the less polar solvents, and the manual conditions could not be directly translated to an automated synthesis. [11C]Methyl triflate ([11C]CH3OTf) was thus used as a methylating agent to increase the conversion at a lower temperature. The 11C-methylation using [11C]CH3OTf at 100 °C proceeded efficiently in THF, 2-MeTHF, and AcOEt with maintenance of the improved selectivity. Starting from 28 to 34 GBq [11C]CO2, [11C]7m6BP was produced with 2.3–2.6 GBq for THF, 2.7–3.3 GBq for AcOEt, and 2.8–3.9 GBq for 2-MeTHF at approximately 30 min after the end of bombardment (n = 3 per solvent). The isolated RCYs (decay corrected) for THF, 2-MeTHF, and AcOEt were 24–28%, 29–35%, and 22–31% (n = 3), respectively. Conclusions The use of THF, 2-MeTHF, and AcOEt improved the [11C]7m6BP/[11C]9m6BP selectivity in the methylation reaction, and the improved method provided [11C]7m6BP with sufficient radioactivity for clinical use.